Akibat Hukum Putusan Penolakan Pkpu Terhadap Debitor (Kajian Hukum Atas Putusan Pengadilan Niaga Jakarta Pusat Nomor: 28/Pkpu/2011/Pn.Niaga.Jkt.Pst.) - Katrin Martha Ulina, Herman Susetyo, Hendro Saptono (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
The Settlement of debt that occured among creditor and debtor could be resolved with two methods, through Bankruptcy and Suspension of Payment (PKPU). Both methods has differences not only process, plea reasons, but also consequnces. PKPU is a certain period that provided by UU through panel of judges of commercial court which on that period creditor and debtor given the opportunity to deliberate a reconciliation plan. This method purposed to avoid debtor from bankruptcy. But, occasionally judges of commercial court rejected to approve reconciliation plan on PKPU. One of example of refusal case and also become object of this research is Verdict of Central Jakarta Commercial Court : 28/PKPU/2011/PN.Niaga.Jkt.Pst.) The purpose of this research are to understand judges consideration to refuse PKPU verdict and also to discover law consequnces which arise from PKPU verdict refusal. Formulation of problems researched by using a research method normative juridical approach with descriptive analytical study. This research conducted with secondary data which consisted of from primary legal material and secondary legal materials. Data analysis method using quatitative analysis technique which is a data analysis that used explanation as theoritical desription and logical estimation, and also difficult to measure with numbers. Based on the research can be obtained that judges consideration which become underline basic of PLPU verdict refusal is reconciliation execution which submitted by debtor not secure enough because of potential investors who involved could not provide accountable responsibility for agreed terms. Beside fee and costs during PKPU has not paid and not being guaranteed for the payment. As stated on Article 285 UUK-PKPU. Therefore. PKPU verdict refusal has legal consequnce, that is bankruptcy verdict on debtor side.